2016
DOI: 10.5331/bgr.16r01
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological and glaciological observations at Suntar-Khayata Glacier No. 31, east Siberia, from 2012-2014

Abstract: ThispaperoutlinesmeteorologicalandglaciologicalobservationsofGlacierNo.31intheSuntar-Khayata Range,eastSiberia,obtainedfrom2012to2014.Wesetupmeteorologicalinstrumentsandsevenstakeson theglacierforthepurposeofmeasuringsurfacemassbalanceandflowvelocity.Themeanairtemperature between July 8, 2012 and August 7, 2013 was-13.9 at site 31-2 (2446m a.s.l.) and the minimum temperaturewas-46.0 .TheairtemperatureontheglacierfromNovembertoAprilwasapproximately 10 higherthanthatatOymyakonvillage,suggestingatemperatureinvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…31 during 2012-2014, showed that the mean and minimum air temperatures were −13.9 and −46.0 • C, respectively, while the accumulated precipitation for one year was 342.0 mm year −1 [8]. Most of the snowfall events occur during the months of spring, summer, and early autumn [8,13,16]. Like other Arctic regions, a significant temperature rise has been observed in the SKMs, especially during winter [1,2].…”
Section: Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…31 during 2012-2014, showed that the mean and minimum air temperatures were −13.9 and −46.0 • C, respectively, while the accumulated precipitation for one year was 342.0 mm year −1 [8]. Most of the snowfall events occur during the months of spring, summer, and early autumn [8,13,16]. Like other Arctic regions, a significant temperature rise has been observed in the SKMs, especially during winter [1,2].…”
Section: Study Areamentioning
confidence: 99%
“…The SKM glaciers were resurveyed in the summer of 2001 [10], while one-year observations were conducted in the mountain range and surroundings from August 2004 to August 2005 using meteorological instruments and ablation stakes [13]. In recent years, continuous glacier monitoring activities have been conducted on SKM glaciers under different initiatives [8,15], which have attempted to re-establish a glacier monitoring system. For instance, Takeuchi and others [15] conducted field measurements of surface melt, reflectivity, impurity features, and their associated impacts on Glacier No.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations